Does your eye keep on the ball?: The strategy of eye movement for volleyball defensive players during spike serve reception - Lee, S.-M. (International Journal of Applied Sports Sciences, 2010)
The current investigation examined the different eye movements used by defenders during spike serve reception in a volleyball game. Six expert and six novice players participated in the experiment. The server exhibited randomized server techniques (spike and ordinary server technique) to defenders. The study required having seven perfect serves received by a defender for data collection from mobile eye trackers to be able to measure/analyze the defender`s eye movements. We analysed the defender's eye movements during the following time period: the time started when a server tossed a ball in the air in preparation to serve to a defender and stopped when the defender made contact with the ball. The time phases were classified into two categories: ball toss phase and flight phase. The results indicated that expert players were more focused on the server`s shoulder and arm region than novice players during the ball toss phase, and experts were faster at tracking a ball than novice players during the flight phase.